The Peran Komunitas Young Entrepreneur dalam Mengembangkan Ekonomi Kreatif Berbasis Syariah Di Kota Makassar - Emily Nur Saidy; Ayu Ruqayyah Yunus; Nurfiah Anwar; Muslihati Muslihati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study analyzes the role of the Tangan Di Atas (TDA) Community in Makassar in developing a sharia-based creative economy. The findings reveal that TDA plays a strategic role in building an Islamic business ecosystem through education, mentorship, halal product innovation, and facilitation of sharia-compliant financing. The community helps young entrepreneurs understand sharia principles such as the prohibition of riba and fair contracts, while also fostering businesses aligned with Islamic values. However, major challenges include limited understanding of sharia principles among members, inadequate access to halal capital, and competition with conventional businesses. This study highlights the importance of collaboration between the community, government, and Islamic financial institutions to create an inclusive and sustainable ecosystem. The findings aim to serve as a reference for developing sharia-based creative economies in other regions.